Design and Performance Analysis of Split Ring Resonator Based Microstrip Antenna With Defected Ground Structure - Köse, Umut; Kavas, Aktül (IEEE, 2020)
In this study, antenna performance improvement has been investigated without changing the antenna size at 2.45 GHz. For the proof of concept, three types of microstrip antenna is designed and simulated at 2.4 GHz. Type I is the conventional microstrip patch antenna which is taken as a reference antenna, Type II is the split-ring resonator based antenna, Type III is the split ring resonator based antenna with defected ground structure. After the numerical analysis and simulation, Type III antenna with the highest gain and bandwidth has satisfied our expectations.
Keywords: Split-ring Resonator-based Antenna; Defected Ground Structure; Microstrip Patch Antenna